2017
DOI: 10.1142/s2047684117500208
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic nonlinear bending response of elastically supported nanotube-reinforced composite beam in thermal environment

Abstract: This paper presents the second-order statistics of the nonlinear bending response of elastically supported single-wall carbon nanotube reinforced composite (CNTRC) beam composed of uniformly distributed (UD) and functionally graded (FG) reinforcements in thermal environments with uncertain system properties. The uncertain system properties such as material properties of matrix and SWCNTs, foundation parameters, thermal expansion coefficients are be modeled as uncorrelated Gaussian random variables. The materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Pradhan [28] used HSDT approach with Eringen to predict the buckling behaviour of isotropic one layer graphene sheet and obtained solution for critical buckling load (CBL). Chaudhari et al [29] performed the thermo-mechanical post buckling analysis utilizing the HSDT with von Karman nonlinearity. Rafiee et al [30] studied response of epoxy/graphene nanocomposite beam experimentally and observed that with small percentage of addition of graphene platelets in matrix improves the performance beam in terms of CBL.…”
Section: Introductionmentioning
confidence: 99%
“…Pradhan [28] used HSDT approach with Eringen to predict the buckling behaviour of isotropic one layer graphene sheet and obtained solution for critical buckling load (CBL). Chaudhari et al [29] performed the thermo-mechanical post buckling analysis utilizing the HSDT with von Karman nonlinearity. Rafiee et al [30] studied response of epoxy/graphene nanocomposite beam experimentally and observed that with small percentage of addition of graphene platelets in matrix improves the performance beam in terms of CBL.…”
Section: Introductionmentioning
confidence: 99%